Does Earning Per Share Contribute to the Effect of ESG Score on Share Price of Mining Sector Companies? - Setyaningsih, Wulan; Surya Wibowo, Riyan (Inovasi Analisis Data, 2024)
Objective: With an emphasis on the moderating effect of earnings per share (EPS) in the mining industry, this study examines the relationship between stock prices and social, governance, and environmental disclosures.Methods: A quantitative examination was carried out with 140 mining companies' data. Information was gathered from MarketWatch, IDX (Indonesia Stock Exchange), and business sustainability reports using documentation methodologies and selective sampling.Findings: The data demonstrates a noteworthy and favorable influence of ESG scores on company prices, with EPS further amplifying this effect. Companies that have high Environmental, Social, and Governance (ESG) ratings experience a rise in their stock prices, particularly when their financial performance is robust. Nevertheless, an unforeseen inverse relationship between earnings per share (EPS) and stock prices within the mining industry indicates that the market is doubtful of the validity of high EPS in specific circumstances.Novelty: This study provides a more profound comprehension of the relationship between financial measures and ESG aspects in influencing stock prices, uncovering the intricate dynamics between financial well-being and sustainable practices.Theory and Policy Implications: The findings underscore the significance of integrating efficient ESG initiatives with robust financial performance in order to enhance stock prices. Policymakers should prioritize the promotion of transparency in reporting environmental, social, and governance (ESG) factors, as well as the incorporation of financial indicators into regulatory frameworks. These measures will help facilitate and encourage sustainable business practices.